The Use of Beauveria bassiana as Biological Control against the Pepper Aphid Insect Pest Myzus persicae Sulz - Semuel Harpandi; Jantje Ngangi; Helen Joan Lawalata; Sukmarayu Pieter Gedoan; Utari Satiman; Yermia Semuel Mokosuli (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
This research is motivated by chilies, which are one of the plant products that become raw materials for daily needs and are therefore classified as a secondary food source. Insect pests are a factor affecting chilli productivity, use of fungi as biological controllers, to determine the use of the fungus Beauveria bassiana as a biological control against the insect pest of chilli aphids Myzus persicae Sulz, the research method used in this study is an experimental method using the complete randomized design (CRD) method with five treatments and three replications, where each plot has five samples, the treatment doses were Control, P1 (6 g/500 ml), P2 (7 g/500 ml), P3 (8 g/500 ml), P4 (9 g/500 ml) and Lethal Dose 50, the results of this study showed that the application of B. bassiana had a significant effect on the mortality of M. persicae Sulz with the mortality obtained was 0.75% of the total number of samples 120 outside the control treatment, so the higher the dose, the higher the mortality, the LD50 result was 6.025 g/ml, showing that the toxicity of B. bassiana falls into the category of mild toxins. Therefore, we can conclude that the fungus B. bassiana serves as an effective biological control agent against the insect pest M. persicae Sulz.